The Video Head Impulse Test in a Case of Suspected Bilateral Loss of Vestibular Function - Albernaz, Pedro L. Mangabeira; Cusin, Flavia Salvaterra (International Archives of Otorhinolaryngology, 2016)
Introduction A patient who had no symptoms suggestive of bilateral loss of vestibular function presented no responses in rotational and caloric tests.Objectives To demonstrate the importance of the video head impulse test in neuro-otologic diagnosis.Resumed Report This patient had a neuro-otologic evaluation and presented no responses in torsion swing tests, caloric tests, and rotational tests in a Bárány chair. The video head impulse test elicited responses in four of the six semicircular canals.Conclusion Absent responses in caloric and rotatory tests alone are not sufficient to diagnose bilateral loss of vestibular function.
Keywords: vestibular diseases; vestibular function tests; head impulse test